Quality By Design dengan Metode Taguchi, Konsep dan Perkembangannya - Moh. Hartono (Jurnal Teknik Industri, 2001)
Industriaml anufactued evelopingis dramaticallpy rogressinngo w followedb y dinamicenvironmentacl hangesT. o give this customerv oices,i ndustrialm anufactureh ave to alwaysincreaseth e quality.I n the otherh andt hereh aveb eenc hangeos f qualityp aradigmath, at's aboutproblems olvinga nd inspectionb, ecomeq ualitye ngineeringin processa nd productw ith Robustdesigna pproachingT. his concepti dea is getting quality processa nd optimump roduct withnoticingn oisef actors,s ot hatt he losso f customercsa nb e minimized.T he Rotrusdt esigni s basedby the needso fdesigni n processa ndp roducth avea strenghtto anu ncontrolledn oisef actors.